A high-content phenotypic screen reveals the disruptive potency of quinacrine and 3',4'-dichlorobenzamil on the digestive vacuole of Plasmodium falciparum. - Lee, Y; Goh, A; Ch'ng, J; Nosten, F; Preiser, P; Pervaiz, S; Yadav, S; Tan, K (2014)
Plasmodium falciparum is the etiological agent of malignant malaria and has been shown to exhibit features resembling programmed cell death. This is triggered upon treatment with low micromolar doses of chloroquine or other lysosomotrophic compounds and is associated with leakage of the digestive vacuole contents. In order to exploit this cell death pathway, we developed a high-content screening method to select compounds that can disrupt the parasite vacuole, as measured by the leakage of intravacuolar Ca(2+). This assay uses the ImageStream 100, an imaging-capable flow cytometer, to assess the distribution of the fluorescent calcium probe Fluo-4. We obtained two hits from a small library of 25 test compounds, quinacrine and 3',4'-dichlorobenzamil. The ability of these compounds to permeabilize the digestive vacuole in laboratory strains and clinical isolates was validated by confocal microscopy. The hits could induce programmed cell death features in both chloroquine-sensitive and -resistant laboratory strains. Quinacrine was effective at inhibiting field isolates in a 48-h reinvasion assay regardless of artemisinin clearance status. We therefore present as proof of concept a phenotypic screening method with the potential to provide mechanistic insights to the activity of antimalarial drugs.